Use of anticoagulant rodenticides: a silent threat to biodiversity in a city of Northern Colombian Andes - Jaramillo-Q., María Antonia; Delgado-V., Carlos A.; Arias-Alzate, Andrés (Frontiers in Ecology and Evolution, 2024)
IntroductionAnticoagulant rodenticides are generalist toxicants that have lethal and sublethal effects on non-target species, leading to an impact on wildlife conservation due to poisoning and bioaccumulation of these substances. However, in Colombia, little research has been conducted on this environmental issue. This study evaluated the use of anticoagulant rodenticides in an urban area in Colombia from an ecological and regulatory perspective.MethodsFirst, the study analyzed the usage patterns of anticoagulant rodenticides for public health in the urban area of Medellı́n over a seven-year period. It also evaluated the potential impact of anticoagulant rodenticides deposits on the city’s Main Ecological Structure and the predator species that may be indirectly affected. Additionally, the study analyzed compliance with regulations on the sale and use of anticoagulant rodenticides in Colombia, specifically for products marketed online. A Hot Spot Analysis was conducted to determine the potential risk of the Main Ecological Structure and the predators selected to be exposed to anticoagulant rodenticides.deposit. On the other hand, the ecotoxicological information of the anticoagulant rodenticides commercialized online in Colombia was characterized, and it was verified whether they complied with the necessary sanitary and environmental national regulations.ResultsBetween 2016 and 2022, over 3 million grams of brodifacoum, were applied in the urban area of Medellı́n and critical ARs hotspots were identified. The use of anticoagulant rodenticides has significantly increased the doses and number of application sites each year. More than half of the points (51.13%) in which anticoagulant rodenticides were applied were within the Main Ecological Structure. The Strigiformes order represents the greatest risk of indirect exposure to anticoagulantrodenticides.DiscussionCurrently, many anticoagulant rodenticide products lack ecotoxicity studies for non-target species and fail to adequately inform consumers of the potential environmental impacts resulting from the use of these poisons. To gain a better understanding of the prevalence, transfer routes, and possible acute and chronic effects of anticoagulant rodenticides.